Cell viability study of star-shaped polymer hydrogel - Ismail, Mohamad Wafiuddin; Muhammad, Taher; Abd Hamid, Shafida; Wan Abdul Khodir, Wan Khartini; Daik, Rusli (2021)
The present study describes the preparation and evaluation of Carbopol formulation incorporated with star-shaped polymer containing PCL and PEG with ciprofloxacin as model drug cargo. The four arms star-shaped PCL-PEG (4PCG) and six arms star-shaped PCL-PEG (6PCG) were formulated to evaluate their capability in hydrogel formulation. Both formulations (4PCG and 6PCG) showed high drug entrapment efficiency (>95%) towards ciprofloxacin mainly due to hydrophobic-hydrophobic interaction between ciprofloxacin and PCL. The formulations were also tested on HGF-1 cell line to check their cell viability. Results showed that the cells maintained their high concentrations (>98%) indicating good biocompatibility.